Morphological and molecular characterization of Corbicula (Mollusca, Bilvalvia) at Rosana Resevoir, Brazil - DOI: 10.4025/actascibiolsci.v27i4.1274 - Bagatini, Yara Moretto (2008)
The purpose of the present study was to verify, using RAPD and ISSR molecular techniques associated with the morphological characterization of bivalve shells, if the morphologically distinct specimens of Corbicula fluminea sampled at Rosana Reservoir belong to different species. The foot muscle tissue of the three groups (G1, G2, and G3) of Corbicula was removed and frozen in liquid nitrogen to the DNA analyze. Morphometric variables of the shell indicated significant differences among the specimens of Corbicula. On the other hand, molecular analyses revealed genetic similarity among the specimens, showing the nonexistence of molecular polymorphism. The data confirmed that the two morphologically different groups also belong to the species C. fluminea, showing the occurrence of phenotypic plasticity, probably caused by environmental or biotic factors